2007
DOI: 10.1007/s00403-007-0779-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the extracellular matrix remodeling by lutein in dermal fibroblasts, melanoma cells, and ultraviolet radiation exposed fibroblasts

Abstract: With aging and cancer there is increased expression or activity of matrix metalloproteinases (MMPs) that degrade and remodel the structural extracellular matrix (ECM). In addition, exposure of skin to ultraviolet (UV) radiation (photoaging) leads to loss of cell viability, membrane damage, and deposition of excessive elastotic material. Lutein has antioxidant, anti-inflammatory, photoprotective, and anti-carcinogenic properties. The goal of this research was to investigate lutein's anti-aging and anti-carcinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 50 publications
3
73
0
1
Order By: Relevance
“…The structural integrity of the ECM is compromised with the increase in the basal or induced levels of MMPs/elastase enzymes as well as their activity with aging or exposure to UV radiation. The ECM proteolytic enzymes (MMPs/elastases) are produced by epidermal keratinocytes, dermal fibroblasts, neutrophils and melanoma cells in the mediation of skin aging or cancer [3,[15][16][17][18]. P. leucotomos extract directly inhibits the activities of MMPs (MMP-1, 2, 3, 9) as well as the cellular expression of MMPs (MMP-1, 2) in nonirradiated or UV radiated dermal fibroblasts or epidermal keratinocytes [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The structural integrity of the ECM is compromised with the increase in the basal or induced levels of MMPs/elastase enzymes as well as their activity with aging or exposure to UV radiation. The ECM proteolytic enzymes (MMPs/elastases) are produced by epidermal keratinocytes, dermal fibroblasts, neutrophils and melanoma cells in the mediation of skin aging or cancer [3,[15][16][17][18]. P. leucotomos extract directly inhibits the activities of MMPs (MMP-1, 2, 3, 9) as well as the cellular expression of MMPs (MMP-1, 2) in nonirradiated or UV radiated dermal fibroblasts or epidermal keratinocytes [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Along with the increase in MMPs, there is decrease in TIMPs with aging or photoaging, which increases the cellular MMPs/TIMPs ratio and ECM damage [9][10][11]18]. P. leucotomos extract stimulates the expression of TIMPs in nonirradiated or UV radiated dermal fibroblasts [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Wondrak et al (2003), repetitive stimulation of the ECM proteins by solar radiation interferes with the integrity of the genome and contributes to photoaging and carcinogenesis of human skin. This excessive exposure to radiation results in the loss of cell viability, cell membrane damage and accumulation of elastotic material that replaces the normal collagen, resulting in a modified architectural pattern in sun-damaged skin known as solar elastosis (Philips et al, 2007). Therefore, the degradation of ECM macromolecules and elastosis increases the risk of developing cancers (Yano et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Lutein and zeaxanthin, which are also called macular xanthophylls, show their effects by filtering high energy visible light, mostly with a peak of absorption at 446 nm and ultraviolet radiation lesser, inhibiting lipid peroxidation and reducing reactive species such as singlet oxygen and hydroxyl radical [46][47][48]. These carotenoids have several benefits on human health, including neuroprotective effects [49][50][51], anti-carcinogenic effects [52][53][54][55], anti-diabetic effects [56][57][58], cardioprotective effects [59][60][61], protective effects on skin damages and ocular diseases [62][63][64][65]. Particularly, several studies showed the role of lutein and zeaxanthin in eye diseases.…”
Section: Introductionmentioning
confidence: 99%